The Monte San Nicola section (Sicily) revisited: A potential unit-stratotype of the Gelasian Stage. (15th February 2022) - Capraro, L.; Bonomo, S.; Di Stefano, A.; Ferretti, P.; Fornaciari, E.; Galeotti, S.; Incarbona, A.; Macrì, P.; Raffi, I.; Sabatino, N.; Speranza, F.; Sprovieri, M.; et al.
Abstract: The Monte San Nicola area (Southern Sicily) offers a spectacular exposure of open-marine sediments that were employed in 1998 for defining the Global Stratotype Section and Point (GSSP) of the Gelasian Stage (Upper Pliocene). After the lowering of the Pliocene/Pleistocene boundary to ca. 2.6 Ma in 2010, the Gelasian GSSP has been redefined as the base of both the Pleistocene Series and the Quaternary Period, which increased its importance and visibility within the scientific community. However, documentation on the Monte San Nicola reference section is still sparse. In the light of its renewed status, we decided to undertake a complete revision of the Gelasian Stage in its type area, in order to evaluate whether the succession of bio- and magnetostratigraphic events that are expected to occur in the interval of relevance are represented adequately in the local record. The results of our investigation demonstrate that the Monte San Nicola succession spans continuously from the upper Piacenzian to the lower Calabrian, and is therefore suitable to host the Unit Stratotype, or even the Astronomical Unit Stratotype, of the Gelasian Stage. Highlights: Two sections from the Monte San Nicola area (Sicily) were studied. The "Type" section (Gelasian Stage GSSP) suffers from local tectonic disturbances. The undisturbed "Mandorlo" section offers a detailed biomagnetostratigraphic record. Astronomical tuning further proves that the section is complete and continuous. The Mandorlo section may host the Astronomical Unit-Stratotype of the Gelasian.